An Attempt to Measure Presentation Skill Acquisition Using Peer and Self-evaluation - Ohno, Isao; Ohkawara, Yuichi; Nakamura, Hitoshi; Morone, Mieko; Suzuki, Tsuneyoshi; Azuma, Yutaka; Sato, Atsuko (YAKUGAKU ZASSHI, 2016)
In six-year pharmacy education programs, humanistic education is now regarded as more important than ever, and we are working to incorporate active learning methods into a variety of subjects. Because performance evaluations are by their nature subjective, it is difficult to ensure the validity of any given assessment. Fifth-year students at Tohoku Pharmaceutical University learn case and prescription analysis in problem-based learning tutorials. As part of this curriculum, 20 presentation and discussion meetings over the course of 10 weeks are held, with approximately 100 students making presentations two or more times each. With regard to the presentation skills that students are expected to acquire, we instructed them to conduct peer evaluations and analyzed the evaluation results for 863 students conducted between 2012 and 2014. From the results, it was found that peer evaluation scores improved between the first and second evaluations for 70% to 86% of students, and furthermore that students who received lower scores in their first evaluations increased their scores correspondingly in the second. In addition, while 87% of students responded positively in the presentation skill acquisition self-evaluations conducted after the completion of the program, there was no correlation between the results of self-evaluation and peer evaluation. It was suggested that many students were able to cultivate an eye for criticism by evaluating other students and gain confidence by becoming aware of their own growth through repeated presentations.